Physical and chemical optimization of a synthetic medium for Pichia pastoris growth - Padrão, Jorge (2006)
The methylotrophic yeast Pichia pastoris is widely used as a host strain for the production of a variety of heterologous proteins. The basal salt medium (BSM) described by Invitrogen (2000) is one of the most broadly used media for this expression system, although it possesses many problems, namely unbalanced composition, salt precipitation and undesirable ionic strength. This medium also uses NH4OH simultaneously, as the nitrogen source and the pH corrector, fact that may be responsible for several growth constrains, namely nitrogen limitation and low protein productivity.